Exploring Financial Culture and Revenue Planning in Small and Medium-Sized Enterprises and Public Sector Entities - Bakos, Tamara; Szőke, Brigitta; Tóth, Eszter; Malatyinszki, Szilárd; Moreno-García, Elena; Lakshmi, Vasantha Patibandla; Jenei, Szonja; Szabó, Róbert; Dávid, Lóránt Dénes (Journal of Ecohumanism, 2024)
This study investigates the relationship between financial culture and financial planning, emphasizing their critical impact on organizational success and economic resilience. Financial culture, defined as the combination of financial knowledge, attitudes, and behaviors, directly influences decision-making, revenue management, and long-term sustainability. Despite global challenges and economic disruptions, the relevance of financial culture persists, particularly in fostering innovation and adaptability within organizations. The research adopts a mixed-methods approach, combining a detailed literature review with in-depth interviews conducted with representatives of SMEs and public sector entities. The literature review highlights disparities in financial literacy and its implications for different sectors, focusing on legislative frameworks, financial decision-making processes, and sustainable financial practices. Primary research findings reveal that SMEs often face challenges such as limited resources and intense competition, while public institutions are shaped by strict regulatory frameworks that emphasize fiscal responsibility. The integration of circular economy principles into financial planning emerges as a significant strategy, offering opportunities to enhance resource efficiency and align financial practices with sustainability goals. Key results demonstrate the importance of financial literacy programs tailored to organizational needs, particularly for SMEs operating in dynamic and resource-constrained environments. Furthermore, adopting circular economy principles proves particularly beneficial in industries such as tourism development, which require sustainable resource management to ensure long-term viability. The findings offer practical insights for policymakers, educators, and business leaders, emphasizing the need for interdisciplinary collaboration to strengthen financial culture. By fostering financial literacy and incorporating sustainable practices, organizations can enhance their economic stability, competitiveness, and contribution to broader societal goals.